Community-Based Religious Empowerment and Family Resilience: The Masturah Program for Divorce Prevention among Tablighi Jamaat Families - Jayusman, Jayusman; Shafra, Shafra; Rahmi, Rahmi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2026)
Divorce rates in Indonesia are high and worrying. Problem-solving is needed to help the government address these issues. The Masturah program for the Tablighi Jamaat in Lampung is the basic capital in the formation of a sakinah family, a harmonious household, and it avoids divorce. The pre-research findings of this program are believed to have helped suppress the divorce rate among Tabligh congregations in Lampung. Whereas, logically, their domestic life is vulnerable to disharmony because husbands often perform khurūj. This paper will further discuss how the Masturah program for the Tablighi Jamaat at Al-Kirom Islamic Boarding School, Kebon Bibit Hajimena, South Lampung, aims to realize a sakinah family and reduce the divorce rate among the Tablighi Jamaat. The findings of this study are the masturah program for the Tablighi Jamaat at Al-Kirom Islamic Boarding School, Kebon Bibit Hajimena, South Lampung, which contains maslahah and is a structured religious development program that fosters sakinah, mawaddah, and a family full of grace, guided by Islamic teachings. This program has succeeded in turning its alumni into more observant couples, maintaining family religious education, and carrying out religious orders. Thus reducing the divorce rate among them.